The Role of the Subplate in Schizophrenia and Autism: A Systematic Review. (1st June 2019) - Serati, Marta; Delvecchio, Giuseppe; Orsenigo, Giulia; Mandolini, Gian Mario; Lazzaretti, Matteo; Scola, Elisa; Triulzi, Fabio; Brambilla, Paolo
Abstract: The subplate (SP) represents a transitory cytoarchitectural fetal compartment containing most subcortical and cortico-cortical afferents, and has a fundamental role in the structural development of the healthy adult brain. There is evidence that schizophrenia and autism may be determined by developmental defects in the cortex or cortical circuitry during the earliest stages of pregnancy. This article provides an overview on fetal SP development, considering its role in schizophrenia and autism, as supported by a systematic review of the main databases. The SP has been described as a cortical amplifier with a role in the coordination of cortical activity, and sensitive growth and migration windows have crucial consequences with respect to cognitive functioning. Although there are not enough studies to draw final conclusions, improved knowledge of the SP's role in schizophrenia and autism spectrum disorders may help to elucidate and possibly prevent the onset of these two severe disorders. Highlights: Subplate (SP) represents a transitory cytoarchitectonic fetal compartment. SP critical maturation period is between the 15th till 24th weeks after conception. SP is visible with Diffusion Tensor Imaging (DTI) and Magnetic Resonance Imaging (MRI). Fetal SP neurons surviving in postnatal period are visible in schizophrenia/autism with MRI. SP residual may alter cortical activity, ultimately affecting cognition.